Psychological well-being in caregivers of the Surakarta Orphanage Muhammadiyah (PAKYM) - Rindu Mahadiva; Ayatullah Kutub Hardew (Jurnal Psikologi Tabularasa, 2025)
Research on psychological well-being of orphanage caregivers has not been widely studied, even though a caregiver needs good psychological well-being to face the challenges of caring for children. This creates a population gap, where research on psychological well-being in caregivers has not been widely studied. So this study aims to determine the description of psychological well-being in caregivers of the Muhammadiyah Family Orphanage (PAKYM) Surakarta. This study uses a qualitative method with a phenomenological approach involving three orphanage caregivers who have been caring for children for more than a year, are mothers, and do not have other jobs besides being caregivers. The research data collection technique used semi-structured interviews, non-participant observation, and documentation. The data analysis used is Interpretative Phenomenological Analysis (IPA). The results of the study showed that 2 out of 3 caregivers experienced psychological problems. While 1 other caregiver was able to enjoy her role as a caregiver. New findings in this study are the mastery of personal emotional conditions and religiosity of orphanage caregivers.